Educação divergente em ciências exatas e tecnológicas: a experiência de uma disciplina remota durante a pandemia COVID-19 - Alves, Alessandra Fernandes (2021)
In this dissertation, I investigate aspects of the didactic field of exact and technological sciences in order to rethink the ideal of scientific objectivity in the direction of a divergent education in exact and technological sciences. The search took place in a remote university extension course, during the COVID-19 pandemic, entitled Diversity in the Education of/in the Exact Sciences. The didactic proposal looked for actions, in the scope of Science Education, that would contribute to the appreciation of student subjectivities, through readings, writings, exchanges of vocal and visual records, debates and performances. The experience is narrated in this text in the form of acts, in a draft script, alluding to the theater and its references. To compose the research body, I chose to organize it in 3 acts: The scientific discourse as technology in the construction of docile bodies; Recognition scenes and performance as resistance in the field of exact and technological sciences. The research was guided by some concepts of Michel Foucault and Judith Butler. And, in the report, it was possible to observe that performativity was an invitation to bodies to find a place of resistance, visibility and subversion of identity in relation to the field of science, in a pandemic context. Also an idea of ​​learning and teaching that cracks a authoritarian programming and theoretically problematizes the assumptions of positivist sciences. There is not a single answer that can be given when thinking about divergent education in Exact Sciences, but here I propose that this can be based on the importance of human subjectivity and in the relationship with different forms of existence, in a creative and inventive dynamic.